Implementasi Konsep Wild into Cozinesspada Perancangan InteriorDog Daycare Center di Surabaya - Charistia Firenze Louis Saputra (Intra, 2016)
Dog is one of the most wanted pets by society. It can be seen from the various competitions that are often held in various cities for dog enthusiasts, especially here in Surabaya. People in Surabaya have such a high demand to have dog as their pets, but there is no place that able to accommodate all the treatments at one place.Dog Daycare Center in Surabaya is hoped to be able provide all dog needs and make the owner’s life easier. Apart from that, this interior design can also be used as a means of relaxation for dog owners and is able to provide a solution that is both informative and educative about the treatment of dogs. The concept used is to bring back the facts that humans and dogs came from two different environments but still able to have a close relationship until there was a term called "men's best friend". Dog Daycare Center have raised the concept of Wild into Coziness. "Wild" is defined as the wild forest which is where the dog grows before used as pet. While the "Coziness", is defined as the human who grew up in an environment that is safe and comfortable. With the application of these concepts in design, it is hoped that the designer can create a place that can be accepted by both sides living creature as the primary users of the facility’s design.